2021
DOI: 10.3390/pharmaceutics13091516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biochemical Evaluation of Baicalein Prodrugs

Abstract: Baicalein (5,6,7-trihydroxy-2-phenyl-4H-1-benzopyran-4-one), a flavonoid analog from Scutellaria baicalensis, possesses several pharmacological activities including antioxidant, antiproliferative, and anti-inflammatory activities. We previously reported that baicalein inhibits the thymic stromal lymphopoietin (TSLP)/TSLP receptor (TSLPR) signaling pathways and can be used as an active ingredient in the treatment of asthma and atopic dermatitis. However, baicalein is rapidly metabolized to baicalin and baicalei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Based on this investigation, the ability of free radical active molecules to trap and scavenge free radicals was tested by preparing six different free radical active molecules’ electrospinning membranes and using them as in situ trapping membranes for atmospheric ROS radicals, which are capable of trapping atmospheric ROS radicals. The free radical active molecules selected in this paper are flavonoids found in natural plants, respectively chrysin [ 38 , 39 ], baicalein, [ 40 , 41 ], scutellarin, genistein, [ 42 ], quercetin [ 43 , 44 ], and baicalin. All have a wide range of pharmacological effects, have antioxidant, free radical scavenging, anti-inflammatory, and anti-tumor effects, have a specific protective effect on the immune, cardiovascular, digestive, and neurological systems, and also have an excellent scavenging effect on reactive oxygen radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this investigation, the ability of free radical active molecules to trap and scavenge free radicals was tested by preparing six different free radical active molecules’ electrospinning membranes and using them as in situ trapping membranes for atmospheric ROS radicals, which are capable of trapping atmospheric ROS radicals. The free radical active molecules selected in this paper are flavonoids found in natural plants, respectively chrysin [ 38 , 39 ], baicalein, [ 40 , 41 ], scutellarin, genistein, [ 42 ], quercetin [ 43 , 44 ], and baicalin. All have a wide range of pharmacological effects, have antioxidant, free radical scavenging, anti-inflammatory, and anti-tumor effects, have a specific protective effect on the immune, cardiovascular, digestive, and neurological systems, and also have an excellent scavenging effect on reactive oxygen radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Several biologics are widely used in clinical practice and are highly effective in patients who do not respond adequately to conventional inhalation therapy or oral steroid maintenance therapy [ 1 , 3 , 13 , 50 ]. However, the efficacy of available biologics depends on type 2 inflammation and, thus, their efficacy in non-type 2 asthma is limited [ 3 , 4 , 5 , 50 , 51 ]. Therefore, detailed treatment strategies for refractory non-type 2 asthma are not yet fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also identified and analyzed bioactive compounds in QF, including baicalin, wogonoside, amygdalin, cryptotanshinone, polydatin, emodin, resveratrol, and baicalein, among others, using UHPLC-MS/MS. Previous studies have shown that these compounds have anti-inflammatory ( He et al, 2020 ), anti-oxidation ( Nagappan et al, 2019 ), anti-allergic, spasmolytic, immune response inhibition ( Bui et al, 2017 ; Son et al, 2021 ) and other effects.…”
Section: Discussionmentioning
confidence: 99%